Comparative study about early full versus conventional partial enteral feeding in preterm new-born infants of 28-34 weeks - Baloda, Mamta; Shah, Maulik; Aravind, Akshay; Bhagora, Nutan (International Journal of Contemporary Pediatrics, 2025)
Background: Enteral feeding is a critical component of neonatal care for preterm infants. Enteral feeding is indicated for a range of medical conditions, including prematurity, where infants cannot suck and swallow effectively; neurological disorders such as cerebral palsy or brain injuries; congenital anomalies like cleft palate; and critical illnesses that prevent adequate oral intake. This study aims to evaluate and compare the outcomes of early full enteral feeding with conventional partial enteral feeding in preterm newborn infants born between 28 and 34 weeks of gestation, focusing on parameters such as growth and development, long term morbidity and mortality. Methods: This is a comparative prospective observational study designed to compare full enteral feeding with partial feeding on preterm. Total 180 preterm infants were included in the study. Participants were allocated into two groups - 90 preterm: full feed, and 90 preterm: partially feed. Results: A study of 180 infants compared full and partial feeding groups, each with 90 babies. The full-feeding group showed fewer complications (16% total) with no necrotizing colitis, while the partial-feeding group had more issues (30.33% total), including 3% with necrotizing colitis. Full-fed babies had better outcomes with higher discharge rates (88% versus 80%) and lower death rates (9% versus 15%). While both groups showed similar length growth, full-fed babies maintained more stable weight gain over 15 days. Conclusions: This study concludes that full enteral feeding is more beneficial approach in the nutritional management of preterm infants leading to improved growth in terms of weight, length and head circumference gain.